Lymphoepitheliale Sialadenitis-artige Thymushyperplasie - Arndt, Börge; Gaiser, Timo; Marx, Alexander (Deutsche medizinische Wochenschrift, 2016)
A 43-year-old man was admitted to this hospital because of shortness of breath and chest pain. The patient had a history of cardiac surgery at the age of seven (due to a congenital heart defect), and of intracerebral bleeding which had occurred at the age of 23. There was no history of autoimmune disorders. Computed tomography revealed a well-circumscribed anterior mediastinal mass, measuring 4 x 3 x 3 cm with calcification and cystic components. Therefore a malignant tumor was suspected for which a thymectomy was performed. Histopathological evaluation revealed an unusual type of thymic hyperplasia strongly resembling lymphoepithelial sialadenitis (LESA) of the salivary glands. A CT scan of the neck, thorax and abdomen for staging did not display lymphadenopathy or splenomegaly. The laboratory tests revealed no abnormality. Clinical, there were no signs of lymphoma. Actually, the patient is in our aftercare. Taken together, lymphoepithelial sialadentis of the thymus is a very rare disorder and was first described in 2012. This disorder seems to be benigne and no other treatment is needed after thymectomy.